Digital Citizenship: Pembatasan Dalam Biometrics Data Collection dan Pelanggaran Hak Asasi Manusia Terhadap Penindasan Kaum Uighur di Xinjiang Oleh Pemerintah Tiongkok - Steven Theonald P. Siahaan; Ika Riswanti Putranti; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2021)
The use of technology to oppress individuals is not a new concept. With the emergence of personal computers and the transition from mass use of radio to television, authoritarian governments have use the technology as a means of spying on their citizens, and China has also become a place where technology are being used to ensure that citizens comply with standards set by an authoritarian government. The Uighurs in Xinjiang are a key example of how modern technology has helped facilitate human rights violations. The government has discriminated the Uighurs and put them in exile camps. Furthermore, the Chinese Government uses biometric data to discriminate the Uighurs, where the Government collects fingerprints, iris scans, put chips inside cellular devices, collect blood groups as well as DNA samples. What is done by the Chinese Government is considered to have violated human rights because it has collected biometric data and abused it for acts of discrimination. Moreover, this act of oppression causing them living life with fear, where they should be living with the freedom from fear. This research seeks to see why restrictions are needed in the practice of Biometrics Data Collection conducted by the Chinese Government. This study uses qualitative research methods with an explanatory method. This research uses the theory of human security, with further emphasizing the personal freedom, particularly the concept of freedom from fear. This research argues that these restrictions are needed and that the practice of collecting biometric data by the Chinese Government on Uighurs in Xinjiang is an act that is based on discrimination and constitutes an act of violation of human rights